Effects of whole body vibration on bone properties in growing rats - Akira Minematsu; Yasue Nishii (International Biomechanics, 2022)
ABSTRACTThis study aimed to examine the continuous effects of whole body vibration (WBV) on bone properties, in growing rats. Fifty 5-week-old male rats were divided into control and experimental groups. Each experimental group underwent WBV at 50 Hz (0.5 g, 15 min/day, 5 days/week) for 5 or 10 weeks. Bone size, muscle weight and bone mechanical strength of the right tibia were measured. Trabecular bone microstructure, cortical bone geometry and bone mass of the left tibia were analyzed by micro-CT. Serum levels of bone formation/resorption markers were also measured. In rats that underwent 5-week WBV, tibial cortical bone mineral content and cortical bone area significantly increased (p < 0.05), and tibial cortical bone volume, thickness, maximum load, break point and stiffness tended to be increased (p = 0.05–0.09), compared with control rats. In rats that underwent 10-week WBV, stiffness tended to be increased (p = 0.07), and the serum level of osteocalcin decreased, compared with control rats. These findings suggest that 5-week WBV had beneficial effects on bone properties, and that increased bone mineral content and cortical bone geometry may lead to higher bone mechanical strength. Further studies will be needed to determine the optimal conditions of WBV for improving bone properties in the growth stage.